Metronomic chemotherapy for advanced breast cancer patients in the real world practice: Final results of the VICTOR-6 study. (December 2019) - Cazzaniga, M.E.; Pinotti, G.; Montagna, E.; Amoroso, D.; Berardi, R.; Butera, A.; Cagossi, K.; Cavanna, L.; Ciccarese, M.; Cinieri, S.; Cretella, E.; De Conciliis, E.; et al.
Abstract: Metronomic chemotherapy (mCHT) refers to the minimum biologically effective dose of a chemotherapy agent given as a continuous dosing regimen, with no prolonged drug-free breaks, that leads to antitumor activity. Aim of the present study is to describe the use of mCHT in a retrospective cohort of metastatic breast cancer (MBC) patients in order to collect data regarding the different types and regimens of drugs employed, their efficacy and safety. Between January 2011 and December 2016, data of 584 metastatic breast cancer patients treated with mCHT were collected. The use of VRL-based regimens increased during the time of observation (2011: 16.8% - 2016: 29.8%), as well as CTX-based ones (2011: 17.1% - 2016: 25.6%), whereas CAPE-based and MTX-based regimens remained stable. In the 1st-line setting, the highest ORR and DCR were observed for VRL-based regimens (single agent: 44% and 88%; combination: 36.7% and 82.4%, respectively). Assuming VRL-single agent as the referee treatment (median PFS: 7.2 months, 95% CI: 5.3–10.3), the longest median PFS were observed in VRL-combination regimens (9.5, 95%CI 88.8–11.3, HR = 0.72) and in CAPE-single agent (10.7, 95%CI 8.3–15.8, HR = 0.70). The VICTOR-6 study provides new data coming from the real-life setting, by adding new information regarding the use of mCHT as an option of treatment for MBC patients. Highlights: Metronomic chemotherapy refers to the minimum biologically effective dose of a chemotherapy agent given as a continuous dosing regimen with no drug-free breaks. In 1st-line, the highest ORR was observed for VRL-based regimens, without any association between clinical or tumor characteristics and ORR. Median TTF was 6.28 months (95% CI: 5.63 – 7.01), regardless of the drug used and median Survival-Post-Progression was 12.0 months (95% CI: 10.4 – 15.6). The longest median PFS were observed in VRL-combination regimens (9.5, 95%CI 88.8-11.3, HR=0.72) and in CAPE-single agent (10.7, 95%CI 8.3-15.8, HR=0.70).